A comparison analysis of the marketing strategy of Lufthansa and Emirates in Germany - Schraub, Isabelle (2019)
The objective of this paper is to perform an analysis of the marketing strategy of Lufthansa and Emirates in Germany. Since both airlines use a similar approach to increase brand awareness an in-depth analysis is implemented in order to identify potential differences. Hereby, consumer insights about the perception and expectation travellers have in common will be analyzed and assessed with quantitative data. Both airlines are well positioned in terms of their marketing strategy, but when Emirates is strengthen its marketing campaign with that pace, the Gulf carrier will certainly make use of its economic strength and can become a frightening threat for the Lufthansa Group on long-haul destinations. Finally, recommendations for future marketing activities for both airlines will be given.